Ancient schwannoma of cervical sympathetic chain masquerading as carotid body tumour - Lim, Chee Chean; Chong, Hon Syn; Yong, Doh Jeing; Foong, Seong Kin; Narayanan, Prepageran (Malaysian Medical Association, 2018)
Schwannoma of cervical sympathetic chain is a rare cause of neck swelling. We report a 73- year-old male presented with anterior neck triangle swelling mimicking a carotid body tumour. Surgical excision was done, and the histopathological examination reported as ancient schwannoma. We would like to discuss the important differential diagnoses and highlight the possibility of an ancient schwannoma of cervical sympathetic chain masquerading as carotid body tumour. Also, to emphasise the importance of imaging for pre-operative planning and counselling.